Tidens landskap: en vänbok till Anders Andrén - Ljung, Cecilia; Andreasson Sjögren, Anna; Berg, Ingrid (Nordic Academic Press, 2019)
"In The Landscape of the Times, 113 researchers are involved in various ways tackle the issues of human science. The book's context shifts from pre-Christian religion, through medieval cities and churches, to historical archeology. Geographically, we move from Egypt to Norrland and chronologically from Stone Age to the present in history's diverse and changing landscape. In the landscape of the time, a palette of central themes and discussions in archeological research is presented, while the substance of the texts highlights the relevance of archeology and how important its findings and contact areas are for other fields of research and society at large+--Publisher website
Enthält Anders Andréns bibliografi (Seite 9-14)
Literaturverzeichnis (Seite 304-344)
Keywords: Andrén, Anders -- 1952-; Festschrift